Experimental analysis on fiber diameter of spunbond nonwoven fabrics through Plackett–Burman and Box–Behnken designs and its impact on mechanical properties - Kaoutar Abdel‐Mouttalib; Ayoub Nadi; Samir Tetouani; Abdelowahed Hajjaji; Omar Cherkaoui; Samira Touhtouh (SPE Polymers)
Abstract The COVID‐19 pandemic sparked a surge in demand for nonwoven protective materials, prompting a significant increase in nonwoven fabric production. To advance understanding, particularly in the Spunbond process, we conducted experiments to analyze the effects of various input parameters on fiber diameter, and mechanical tests to study how fiber diameter influences the mechanical properties of spunbond nonwoven fabrics. Employing Plackett–Burman design and Box–Behnken design with Minitab 18, we have examined different process parameters and study the cause‐and‐effect relationships between input parameters and the response. A set of experiments were carried out with nine varying parameters, including polymer melt index, initial polymer temperature, and air velocity. By regression modeling, we assessed the effects and interactions of these factors on fiber diameter. The Box–Behnken approach revealed that only three factors significantly influenced fiber diameter. Our analysis unveiled valuable insights for optimizing process parameters to achieve a target fiber diameter of 31.0 μm, crucial for enhancing nonwoven fabric production. Moreover, the results of the tensile property tests show that fiber diameter influence mechanical properties of nonwoven fabrics. As the fiber diameters increase, the mechanical properties of the nonwoven fabric are increased. Highlights Market research of textile industry, particularly of nonwoven sector. Identification of the parameters of the Spunbond process. Selection of Placket–Burman and Box–Behnken designs to analyze, optimize, and predict fiber diameter. Evaluation of the designs results (analysis of variance, Pareto, Regression model …), determination of the optimal conditions and the factors that has most effect on fiber diameter. Investigation of the effect of fiber diameter on mechanical properties.